KERAPATAN DISLOKASI / LATTICE STRAIN PADA ALUMINIUM YANG DI DEFORMASI PLASTIS DENGAN LAJU REGANGAN TINGGI - AMINNUDIN
One of method to increase strength of aluminum is reduce grain size from recrystalisation process. To produce small grain size needs many places to nuclei. Dislocation is one of location nuclei can occur. Aluminum with high dislocation density can produce small grain size with recristalisation process. Aluminum has FCC (Face Centered Cubic) crystal structure and has very high stacking fault energy. When plastics deformation done to aluminum, dislocation at aluminum will move easily so increasing dislocation density do not high. Dislocation difficult to move at low temperature, plastics deformation at low temperature will increase dislocation density. There is main topic of this thesis. Plastics deformation used impact test machine at temperature 25, 0, - 25, -50, -75 and -100 `C. Data from test result, lower temperature of plastics deformation will produce higher hardness of aluminum. Data of dislocation density front ,l- Ray Diffraction (X-RD) detection showed highest dislocation density resulted from specimen with plastics deformation at lowest temperature.